2020
DOI: 10.1186/s41118-020-00074-7
|View full text |Cite
|
Sign up to set email alerts
|

Childlessness and low fertility in context: evidence from a multilevel analysis on 20 European countries

Abstract: Low fertility and childlessness have been largely interpreted as being driven by the same mechanisms, although they may be qualitatively different phenomena. The present article discusses this assumption and studies determinants of childlessness by comparing them with determinants of low fertility. Drawing on micro-level data from the European Labour Force Survey (2005-2010) and macro-level data from external data sources, it enters the debate on the micro-and macro-determinants of fertility and childlessness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 124 publications
1
4
1
1
Order By: Relevance
“…Substantial advances in information and communications technology have significantly changed most aspects of human life and led to the modeling of behaviors of others and the behaviors portrayed in media 12 . However, our findings contradict the findings of a former study which reported that the use of social networks had no significant effects on childbearing tendency 56 . This contradiction is due to the fact that our participants were both men and women aged 18–49 years while that study was conducted only on young women.…”
Section: Discussioncontrasting
confidence: 99%
“…Substantial advances in information and communications technology have significantly changed most aspects of human life and led to the modeling of behaviors of others and the behaviors portrayed in media 12 . However, our findings contradict the findings of a former study which reported that the use of social networks had no significant effects on childbearing tendency 56 . This contradiction is due to the fact that our participants were both men and women aged 18–49 years while that study was conducted only on young women.…”
Section: Discussioncontrasting
confidence: 99%
“…Yet, (also) to account for this potential bias, our analyses report age-specific estimates. Notwithstanding the noted shortcomings, the 'own child method' is sufficiently well established in the literature (Brini, 2020;Krapf & Kreyenfeld, 2015) and results in figures comparable with other fertility estimates, both at the national and regional level in Italy (see Bordone et al, 2009). 8 All models include controls for education (up to lower secondary level, upper secondary level, or tertiary level), education-specific non-parametric time trends, marriage status (married or cohabiting), immigration background (native or migrant) and we report results separately for men and women.…”
Section: Data and Variablessupporting
confidence: 61%
“…Observed sexually antagonistic selection on educational attainment is consistent with most previous studies that are based on population registries (although in some countries, educational differences in childlessness among women appear to have diminished or disappeared over time as reviewed by Refs. 24 and 55). We found that odds of having a first child were independent of the educational attainment of women, while education above primary was associated with lower odds of progression to parities above one and two.…”
Section: Discussionmentioning
confidence: 98%